Beyond Boundaries: Painting Re-inscriptions in the Fifteenth to Seventeenth Century China - Wang, Wenxin (Arte, individuo y sociedad, 2024)
This paper explores the widespread practice of adding multiple inscriptions to a single artwork at different times in the fifteenth to seventeenth centuries China. Such practices became prominent when literati painters revisited artworks they had previously created or owned, or when paintings had accumulated a multitude of inscriptions over time. Within the realm of Chinese art discourse, this phenomenon is denoted as “re-inscriptions.” By examining re-inscriptions written on extant paintings and embodied in individual anthologies, this paper demonstrates that these texts transcended the boundaries of art and touched upon the painters’ own lives and the society in which they lived. On the one hand, literati painters engaged in a dialogue with their past selves through re-inscriptions, exploring themes of mortality, aging, and the passage of time – topics seldom addressed in traditional Chinese painting. On the other hand, they utilized re-inscriptions as a means of social interaction, with some re-inscriptions becoming formulaic, adaptable to various artworks to meet different social needs. Furthermore, when faced with preexisting inscriptions on an artwork, artists added new ones for a conversation with their predecessors. Throughout this process, the accumulation of inscriptions transformed the artwork into a layered cultural narrative, and enabled the literati painters in shaping a elite community transcending time and space.